The Influence of Additive Manufacturing Processes on the Performance of a Periodic Acoustic Metamaterial - Bennett, Gareth; Kennedy, John (My University, 2019)
Advancements in 3D print technology now allow the printing of structured acoustic absorbent materials at the appropriate microscopic scale and sample sizes. The repeatability of the fundamental cell unit of these metamaterials provides a pathway for the development of viable macro models to simulate built-up structures based on detailed models of the individual cell units; however, verification of such models on actual manufactured structures presents a challenge. In this paper, a design concept for an acoustic benchmark metamaterial consisting of an interlinked network of resonant chambers is considered. The form chosen is periodic with cubes incorporating spherical internal cavities connected through cylindrical openings on each face of the cube. This design is amenable to both numerical modelling and manufacture through additive techniques whilst yielding interesting acoustic behaviour. The paper reports on the design, manufacture, modelling, and experimental validation of these benchmark structures. The behaviour of the acoustic metamaterial manufactured through three different polymer-based printing technologies is investigated with reference to the numerical models and a metal powder-based print technology. At the scale of this microstructure, it can be seen that deviations in surface roughness and dimensional fidelity have a comparable impact on the experimentally measured values of the absorption coefficient.
PUBLISHED
Keywords: 3D print technology; Acoustic metamaterial; Nanoscience & Materials; Smart & Sustainable Planet; Metamaterial